God and the Grounding of Morality. - Nielsen, Kai. (Ottawa : University of Ottawa Press, 1997)
These essays make a single central claim: that human beings can still make sense of their lives and still have a humane morality, even if their worldview is utterly secular and even if they have lost the last vestige of belief in God. "Even in a self-consciously Godless world life can be fully meaningful," Nielsen contends.
CHAPTER 11 God and the Basis of MoralityIndex.
Print version record.
Added to collection customer.56279.3
Keywords: Religion and ethics; Natural law; Human rights -- Moral and ethical aspects; RELIGION -- General; Human rights -- Moral and ethical aspects; Natural law; Religion and ethics; Electronic books